Redesigning Learning for Greater Social Impact Taylor's 9th Teaching and Learning Conference 2016 Proceedings (Springer Singapore, 2018)
These conference proceedings explore the design of pedagogical intervention and learning cultures, the inclusion of socio-emotional support in teaching and policy, transforming technology to support the social fabric of our institutions, and challenging established beliefs about learning. They clarify the complex challenges involved in employing social learning in education and higher education institutions to foster greater understanding and insights, while also avoiding the pitfalls that come with rolling out the concept of "redesigning learning". The Taylor's Teaching and Learning Conference has been held at Taylor's University, Malaysia, since 2006.